Valor del índice de resistencia por ecografía Doppler en predicción de malignidad de nódulos tiroideos en el Hospital Víctor Lazarte Echegaray - Valdez Gallo, Edilfonso (2022)
Nodular thyroid diseases are the most frequent diseases of the thyroid gland. The prevalence of clinically apparent thyroid nodules is 5% in women and 1% in men living in iodine-deficient regions of the world. However, two decades ago, the widespread use of ultrasound has resulted in a dramatic increase in thyroid nodules, estimated at 19%–68% in the general population1. The high prevalence of thyroid nodules requires evidence-based rational strategies for differential diagnosis, risk stratification, treatment, and follow-up. These strategies focus primarily on the risk of thyroid malignancy. Carcinoma is the most common cancer of the glandular endocrine system and constitutes 1% of human neoplasms. The incidence of thyroid cancer has almost tripled from 4.9 per 100,000 to 14.3 per 100,000 in approximately 35 years, such an incidence is higher if cases of occult carcinoma are taken into account. Advanced age, male sex, radiation. exposure, rapid growth of neck mass, nodule > 4 cm, and family history of thyroid cancer are the main risk for malignant thyroid lesions3. Ultrasonography uses a wide range of characteristics that have different values of sensitivity and specificity in the prediction of thyroid cancer. However, none of them could be used alone to efficiently detect or reject malignancy. The main disadvantage of ultrasound is its specificity. relatively low and substantial variability between operators8. Some authors have already demonstrated the possibility of distinguishing thyroid diseases and predicting their prognosis based on duplex color Doppler ultrasound. These distinctions are usefully functional, because duplex color Doppler is noninvasive and does not involve ionizing radiation9. Therefore, to understand the pathophysiology. of diseases whose vascularization is modified, the normal definition of the reference parameter is essential10. The Color Doppler technique evaluated the vascular status of nodules (intranodular or perinodular vessels), by calculating the Resistance Index (RI), Pulsatility Index (PI) and Mean Systolic Velocity (MSV); Peak Systolic Velocity (PSV) and End Diastolic Velocity (EDV); the resistance index is the result of the quotient between the difference of the peak systolic velocity minus the final diastolic velocity; on Peak Systolic Velocity11.